HAPLOTYPE DIVERSITY IN THE PARTIAL CYTOCRHOME B (CYTB) GENE OF WATER MONITOR LIZARDS (Varanus salvator) AT PENINSULAR MALAYSIA: A SHORT COMMUNICATION - Muhammad Kemal Ariq Naufal Ramadhan; Widya Pintaka Bayu Putra (Jurnal PPI Dunia, 2022)
Water Monitor (WM) lizard (Varanus salvator) are one of Varanidae family lizard that widely spread at Southeast Asia belonging to Peninsular Malaysia. This research was conducted to observe the halotype diversity in partial mitochondrial Cytochrome b (Cytb) gene (344 bp) of WM lizards at Peninsular Malaysia. A total of seventeen (17) Cytb sequences of WM lizard were collected from NCBI database. Research showed that five (5) haplotypes of Cytb gene were observed in the observed sequences. About 71% of WM lizards from Peninsular Malaysia were classified into Haplotype 3 (Hap.3). Hence, this haplotype was classified as the common ancestral of WM lizard at Penensular Malaysia. The Neutrality test revealed that low allelic frequency in WM lizard can be caused by species expansion. In conclusion, the WM lizards at Peninsular Malaysia consisted of two (2) clades of Clade A (Hap.1 and Hap.2) and Clade B (Hap.3, Hap.4 and Hap.5).